Strengthening E-Learning Literacy for Vocational School Students in the Pangandaran District - Nalahuddin Saleh; Syihabuddin; Yayan Nurbayan; Hikmah Maulani; Shofa Musthofa Khalid; Anwar Sanusi; Eneng Komariyah Maimun Ratma Ningrum Maharani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This community service aims to determine the efforts that must be made to strengthen e-learning literacy for vocational students in Pangandaran Regency. This community service method used is descriptive qualitative. Data analysis techniques used are interviews, observation and dedication. The data analysis technique uses the Miles and Huberman technique, namely, 1) Data collection, 2) Data reduction, and 3) Verification and conclusion. The result of this study was the discovery of the inability of students and teachers at Pangandaran district Vocational Schools regarding digital E-learning literacy, so reinforcement from students whom the government assisted, institutions and teachers were needed to make this happen. One of the efforts students must make is to understand and study technology and explore teaching resources sent by teachers and discussions in e-learning forums to hone student literacy.